If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (15 + 3x) + -3x = 0 Remove parenthesis around (15 + 3x) 15 + 3x + -3x = 0 Combine like terms: 3x + -3x = 0 15 + 0 = 0 15 = 0 Solving 15 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| w^2=7w | | 6m+5n=-32 | | 4x-5=12x-45 | | 8x^3+36x^2+40x+12=0 | | 9d=27 | | -7x+9(-4)=-15 | | 56=8(x+3) | | -4+y=20 | | 7=s/2+5 | | (x*x)+(x*x)=2116 | | 10d+6=6d+22 | | X^2+bx+64= | | 122-2x=6x+16 | | 3(t+2)=2-(2t-2) | | 10x-23=77 | | 2(3x+4)=2(4x+1) | | 4x^3+15x^2+37x+39=0 | | 3-2k=-9 | | 8v-10=105 | | (x+1)(x-7)=0 | | 8r^2-12r=0 | | 0=-16x^2+3x+1.3 | | 3x^2+34x+80=0 | | 18=3(d-1) | | 3-4(x+2)=15 | | x^3+x^2-x-1.7=0 | | 3a-32=-2a+23 | | 7(-6y+9)+4y=-13 | | (x*x)+(x*x)=36 | | 137-4x=23x+23 | | 20.4-2c=5 | | 4x+y+1=-y-2x+3 |